Social Work and the Organizing of Transition to Work - Christian Schröder (Social Work and Society)
Against the backdrop of results of a research project on career guidance services, I will hold the opinion that these services have become part and partial of reproducing a"social reality centred on the distinction between employees and job seeker. In this reality, the category of labour predominantly defines who is considered as a normal citizens and who is considered an outcast or even a parasite of the social welfare system. Even despite the fact of the high unemployment rate and growing precarious working relationships in the EU, gainful employment is seen as the most natural thing in the world. The drawing of the distinction between inside and outside of society by gainful employment, then, masks social inequalities. The paper develops the argument in four consecutive steps. After an introduction into transitions to work and the role of career guidance, methods and empirical data is presented. This is, thirdly, followed by the presentation of some major results of the project.  Eventually, I will link the results to current political discourses and development.